A global panel analysis comparing carbon emissions across levels of economic development - Tiono, William; Mulia, Ni Pryanka; Kadarusman, Yohanes Berenika; Ramadhanti, Fati (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
This study compares carbon emissions across panels of high-income countries (HICs) and low- and middle-income countries (LMICs). Using the Environmental Kuznets Curve (EKC) hypothesis as a theoretical framework, this study observes the curve for each income panel using random effects panel regression, controlling for the scale, composition, technological, and pollution outsourcing effects. With a dataset ranging 30 years from 1990 to 2019 and a panel of 18 HICs and 20 LMICs, the regression results validate the presence of an EKC-like relationship between emissions and income per capita for both panels. Key findings show that LMICs are on a path of growth that emits fewer emissions than HICs at the same income level due to access to less emission-intensive technologies. This suggests that, in contrast to previous theoretical understanding, the effects observed in the EKC occur simultaneously rather than sequentially and may be leveraged to dominate at any point on the curve. In practice, LMICs are urged to dismiss the “grow now, clean later” ethos and instead, adopt cleaner production methods through energy efficiency initiatives, technological transfers, and technological leapfrogging to manage economic growth without a corresponding growth in emissions. Keywords: environmental Kuznets curve; panel data; robust random effects; carbon emission JEL Classification: Q56; O44